DAMPAK AKUISISI PT PERUSAHAAN PERKEBUNAN LONDON SUMATRA. TBK OLEH PT INDOFOOD SUKSES MAKMUR. TBK - , Pemi Hari Utami, Dr. Erni Ekawati, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Acquisition (acquisition) is a merger where one company, the acquirer (acquirer) gain control of the net assets and operations of the acquired company (acquiree), by giving certain assets, recognizes an obligation, or issuing shares. In other word, acquisition is purchasing activity of investor company to the acquiree company. There must be some motives from acquisition, for instance increasing the companyâs value, gaining competitive advantages in the retail industry, increasing efficiency in operational costs, strong financing, management and technology (synergy). PT. Alfa Retailindo Tbk. formerly Alfa Gudang Rabat or Alfa Supermarket, a modern retail store which has become a public company in Bursa Efek Indonesia since 2000, was also been acquired by gaining strong synergy from PT. Carrefour Indonesia, the second largest modern retail store from France to counter high competition in Indonesia retail industry. On 21 January 2008, PT. Alfa Retailindo Tbk. has sold 351 million shares of ALFA (75%) to PT. Carrefour Indonesia or equal to Rp674 billion or 49,3 million euro, or Rp1.921 per share. Until 15.01 Bursa Efek Indonesia JATS time on the day of acquisition, ALFA shares was on level Rp2.050 per share. There is Rp129 different point between selling price Rp1.921 and market price Rp2.050. This leads to the question whether ALFA shares have been sold in fair price. This tesis will examine the effect of PT. Alfa Retailindo Tbk. (ALFA) acquisition by PT. Carrefour Indonesia by calculating the companyâs financial performance before acquisition from 2002 to 2007 and projected financial performance after acquisition from 2008 to 2015. The thesis will also calculate the companyâs valuation or the fair value of ALFA by using discounted cash flow method.